1975
DOI: 10.1063/1.322219
|View full text |Cite
|
Sign up to set email alerts
|

Small−angle x−ray−scattering study of microstructure of polyvinylchloride

Abstract: Small-angle x-ray-scattering (SAXS) measurements were made on polyvinylchloride ftlms which were stretched and/or annealed. The SAXS data showed only monotonically decreasing continuous-type scattering which varied according to the time and temperature of thermal treatment and to the amount of ftlm extension. It was concluded from the analysis of these data that annealing and stretching have a relatively small effect on the size of the scattering regions, the major effect being due to the variation in electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1976
1976
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Their obtained values are in the region of only 0.5% or less. Other studies using SAXS (26,27) concluded that a two-phase structure exists in PVC and that when PVC is annealed above Tg, the ordered structure is enhanced. Ohta, Kajiyama, and Takayanagi (28) used differential scanning calorimetry (DSC) to determine a maximum value of 5.7% crystallity, when PVC is annealed at 130°C.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Their obtained values are in the region of only 0.5% or less. Other studies using SAXS (26,27) concluded that a two-phase structure exists in PVC and that when PVC is annealed above Tg, the ordered structure is enhanced. Ohta, Kajiyama, and Takayanagi (28) used differential scanning calorimetry (DSC) to determine a maximum value of 5.7% crystallity, when PVC is annealed at 130°C.…”
Section: Introductionmentioning
confidence: 97%
“…The structural order in rigid commercial PVC has been investigated by many with frequent lack of agreement among workers with regard to the nature of the structure (19)(20)(21)(22)(23)(24)(25)(26)(27)(28). In 1956 Natta and Corradini (19) indicated that PVC is a polymer of fairly low degree of crystallinity and of relatively low perfection.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] By varying the incidence angle, samples can be probed on thickness going from atomic scale to few micrometers. Benefiting from the penetration capacity of x rays and the weak absorption of this kind of polymers, the diffuse reflection and the transmission of x radiations will be used in complementarity.…”
Section: Introductionmentioning
confidence: 99%